1+4a=-5+3a

Simple and best practice solution for 1+4a=-5+3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+4a=-5+3a equation:


Simplifying
1 + 4a = -5 + 3a

Solving
1 + 4a = -5 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
1 + 4a + -3a = -5 + 3a + -3a

Combine like terms: 4a + -3a = 1a
1 + 1a = -5 + 3a + -3a

Combine like terms: 3a + -3a = 0
1 + 1a = -5 + 0
1 + 1a = -5

Add '-1' to each side of the equation.
1 + -1 + 1a = -5 + -1

Combine like terms: 1 + -1 = 0
0 + 1a = -5 + -1
1a = -5 + -1

Combine like terms: -5 + -1 = -6
1a = -6

Divide each side by '1'.
a = -6

Simplifying
a = -6

See similar equations:

| 5n-3=92 | | 5+4z-7=4z-2-z | | 3x-2=9-8x | | 576(72)=d | | x^4-7x^2+20=0 | | 5x+8=6x | | 2x+y-2z=-3 | | 1.6/24=n/60 | | 3y/8-2=4 | | 2v^2+7v+5= | | 4-5n=2-3n | | -4x+4-30-18x=.33 | | w^2+4w= | | 8k-=23-k-3k | | 5x-4=3n+2 | | K-5/6=-7 | | 2t=-13 | | 16s^2+24s+9= | | 3(2)+6(8+2)= | | B+10.8=12.80 | | 10=s/2+78 | | 1/3x=6-1/5x | | 3x+2(x+1)=6x+(3x-4) | | 7n-20=-48 | | c^2+14c+45= | | m^2+6m+4=-4 | | 4i(6+2i)= | | y=3.0x+1.7 | | 6x+3=12-2x | | t(5t+2)= | | 276/12 | | Y=6x^2+x-15 |

Equations solver categories